Analisis Hukum terhadap Kebijakan Pencegahan dan Penanganan Kasus Bullying di Lingkungan Sekolah “Perspektif Perlindungan Hak Anak" - Irawati, Sri Ayu; Wachyana, M. Wahid (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Cases of bullying in the school environment are a serious concern in the context of protecting children's rights. This research aims to conduct a legal analysis of policies for preventing and handling bullying cases in the school environment, with a focus on the perspective of protecting children's rights, especially in the Taman Harapan Malang Senior High School (SMA) environment. The research method used is literature study and tracing policies and regulations related to child protection and handling bullying cases in schools. Analysis was carried out on legal, policy and implementation aspects in the field. The research results show that although there are various policies and regulations aimed at preventing and handling bullying cases, their implementation still has significant challenges. Factors such as lack of awareness, limited resources, and lack of training for education actors can hinder the effectiveness of such policies. Therefore, more serious and coordinated efforts are needed from various parties, including the government, schools and society, to ensure the protection of children's rights from cases of bullying in the Taman Harapan Malang school environment.